Bacterial Community in Cold Surge-Caused Sea Ice Differs From Seawater in Mid-Latitude Region: A Case Study in Aoshan Bay, Southern Yellow Sea - Ren, Hongwei; Liu, Jihua; Li, Gang; Hu, Yubin (Frontiers in Marine Science, 2022)
Cold surges result in a rapid drop in air temperature and freezing of seawater, which was likely to impact bacterial communities. We examined the differences in bacteria abundance and bacterial community composition in the sea ice and seawater during a cold surge along Aoshan Bay, southern Yellow Sea in January 2021. Results showed that the differences in bacteria abundance between sea ice and seawater likely resulted from the physical impact of ice formation. The parent water played a key role in bacterial community composition in the early phase of ice formation, in which bacterial community compositions at class level were similar, but the relative abundances were different between sea ice and seawater. The Gammaproteobacteria dominated in sea ice, and the relative abundances of Verrucomicrobiae were also significantly higher, possibly due to the high concentration of algal-derived DOM in coastal areas. The predicted functional profiles suggested the lower abundance of functional genes related to ATP-binding cassette transporters in sea ice than in seawater, which might be due to the bacteria not requiring varieties of functional genes of ATP-binding cassette transporters in restricted sea ice brine.